Exploring the role of financial ratio and interest rate on banking credit channelling: Data from Indonesia - Idah Zuhroh; Frinda Pramesti Regitara Cahyani (Jurnal Inovasi Ekonomi, 2021)
This study explores the effect of financial ratio and benchmark interest rate on the determinants of credit channelling in Indonesia. The data in this study uses quarterly data during the 2010-2019 period; the analysis technique in data processing uses panel data regression. The results of this study indicate that the model is simultaneous significant. Third-party funds and loan to funding ratio partially have a significant positive effect. Operating expenses and operating income have a significant negative impact. The benchmark interest rate has not substantially influenced the determinants of bank lending in Indonesia.